All the gospel to all the world: 100 years of Assemblies of God Missiology - Lewis, Paul; Klaus, Byron D. (The J. Philip Hogan world missions series, 2014)
1914 to the 1970s: Foundational Voices -- 1980s to the 1990s: Elaborating Voices -- 2000 to 2014: Global Voices.